The Relevance and Challenges of the Insurance Industry in Contemporary Administration: A Call for Researchers - João Vinícius de França Carvalho; Eduardo Flores; Emiliano A. Valdez (RAC: Revista de Administração Contemporânea, 2021)
The insurance industry is one of the most relevant segments for sustainable economic development, not only because it protects society’s assets, but also because it encourages the formation of long-term provisions and reserves. Thus, it is possible to guarantee that advances in income distribution, as well as family consumption, will not regress under adverse scenarios. By promoting virtuous feedback between the productive activity and the legitimate social interest, this sector plays a central role in the promotion of collective well-being. Therefore, Actuarial Science can strongly collaborate in the development of Contemporary Administration.